2000
DOI: 10.1177/03635465000280051901
|View full text |Cite
|
Sign up to set email alerts
|

Refracture of Proximal Fifth Metatarsal (Jones) Fracture After Intramedullary Screw Fixation in Athletes

Abstract: This study details six instances of refracture of clinically and radiographically healed fractures of the base of the fifth metatarsal after intramedullary screw fixation. Four professional football players, one college basketball player, and one recreational athlete underwent intramedullary screw fixation of fifth metatarsal fractures. The athletes were released to full activities an average of 8.5 weeks (range, 5.5 to 12) after fixation, when healing was clinically and radiographically documented. Three foot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
253
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(261 citation statements)
references
References 13 publications
7
253
0
1
Order By: Relevance
“…Several studies have suggested acute forefoot injury as the cause of Jones fractures, whereas physiologic repetitive stress injury is most likely responsible for proximal diaphyseal fractures of the fifth metatarsal [4,17,19,22]. However, all of these studies lack appropriate statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have suggested acute forefoot injury as the cause of Jones fractures, whereas physiologic repetitive stress injury is most likely responsible for proximal diaphyseal fractures of the fifth metatarsal [4,17,19,22]. However, all of these studies lack appropriate statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The Jones fracture initially was described by Sir Robert Jones in 1902 [7], and a review of his article showed both fracture types are included in his clinical cases and radiographs. More recent literature defines differences in diagnosis and prognosis between acute Jones and proximal diaphyseal stress fractures [11,[20][21][22]. A Jones fracture currently is defined as an acute fracture of the fifth metatarsal at the junction between the proximal diaphysis and metaphysis of the fifth metatarsal without distal extension beyond the fourth to fifth intermetatarsal articulation [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These fractures are devastating to athletes because they are slow to heal and have a high potential for delayed union, nonunion, and refracture. 4,9,[14][15][16][17][18][19]26,28 These fractures can be acute, stress, or combined acute/stress fractures of the proximal portion of the fifth metatarsal. The Jones fracture 4,8 was first described by Jones in 1902 13 and involves the proximal third of the fifth metatarsal, distal to the insertion of the fibularis (peroneus) brevis tendon, 1.5 cm from the tuberosity of the fifth metatarsal (figure 1).…”
mentioning
confidence: 99%
“…55 Running shoes with neutral insoles have recently demonstrated a statistically significant reduction in plantar pressure in athletes with cavus feet (A). 56 In relation to refracture, it is well known that returning to sport early is an important risk, therefore athletes should be warned about the complication (C). 47,57 In high level athletes, computerized tomography or magnetic resonance imaging should be considered before returning to training in order to avoid refracture (C).…”
Section: What Are the Indications For Surgical Treatment?mentioning
confidence: 99%